2013
DOI: 10.3171/2012.10.peds12160
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal skull base surgery in the pediatric population

Abstract: Object The use of endoscopic endonasal surgery (EES) for skull base pathologies in the pediatric population presents unique challenges and has not been well described. The authors reviewed their experience with endoscopic endonasal approaches in pediatric skull base surgery to assess surgical outcomes and complications in the context of presenting patient demographics and pathologies. Methods A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
139
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 72 publications
(117 reference statements)
2
139
0
11
Order By: Relevance
“…Feasibility of these approaches in children has been demonstrated. 4,8,9 However, successful EEA surgery requires an adequate working space for the endoscope as well as the instruments. Hesitations and questions have been raised regarding the feasibility of performing EEAs in pediatric patients, given the smaller working space compared with adults.…”
Section: 19mentioning
confidence: 99%
“…Feasibility of these approaches in children has been demonstrated. 4,8,9 However, successful EEA surgery requires an adequate working space for the endoscope as well as the instruments. Hesitations and questions have been raised regarding the feasibility of performing EEAs in pediatric patients, given the smaller working space compared with adults.…”
Section: 19mentioning
confidence: 99%
“…Two patients (1.2%) developed a CSF leak, which is comparable to the 1.3% rate noted in other pediatric neurosurgery studies that have used PEG sealant (range 1.3%-17.5%). 4,6,11,14 Other studies examining CSF leak rate with PEG sealant were limited to adult cohorts but also reported a comparable leak rate. Boogaarts et al reported a 2.2% CSF leak rate in a nonrandomized, prospective trial; 2 Cosgrove et al, 1.8% in a prospective trial; 5 Weinstein et al, 7.6% in a retrospective review; 15 Than et al, 2% in a prospective review; 13 and Osbun et al, 0.8% in a prospective randomized trial.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8]11,14 Although the safety of adjunctive closure techniques has been extensively studied in the adult population, few studies have evaluated the efficacy and/or safety of sealants in the pediatric population. …”
mentioning
confidence: 99%
“…5,18,19,32,41 For properly selected tumors, EES offers several advantages over traditional methods, including the sparing of disfiguring facial incisions and craniotomy. EES allows the surgeons to access the entire ventral skull base, from the crista galli to the upper cervical spine, with minimal postoperative complications.…”
mentioning
confidence: 99%